The role of banks in monetary policy transmission: empirical evidence from Russia - Tuuli Juurikkala; Alexei Karas; Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
This paper focuses on the role of the banking sector in monetary policy transmission in an emerging economy with a rapidly developing financial system. Specifically, we exam whether the central bank's monetary policy stance affects banks' lending behaviour. Based on a comprehensive quarterly dataset on all Russian banks from 1Q1999 to 1Q2007, we find evidence for the existence of a bank lending channel in Russia. Contrary to several studies on developed economies, the level of a bank's capitalization matters for the transmission process. Better capitalized banks are less likely to adjust their lending practices following a change in the monetary policy stance.
URN:NBN:fi:bof-201408072171
Keywords: Q19; Q20; 330